Integrasi Kearifan Lokal dan Revolusi Industri 5.0: Inovasi Manajemen Perpustakaan - Ali Hasan, Nurhayati; Mujiburrahman; Mahmud, Salami; Safrilsyah (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The Fourth Industrial Revolution introduces a new paradigm that emphasizes synergy between humans and technology across various fields, including library service management. Library service management based on local wisdom is the transformation of libraries into modern knowledge centers that preserve cultural identity. This paper attempts to analyze the readiness for integrating local wisdom into innovative library service management in the face of the 5.0 Industrial Revolution, as well as the challenges libraries face in addressing the 5.0 Industrial Revolution. The method used is a literature review with a qualitative approach. The results of the study indicates most libraries realize the importance of integrating local wisdom with technology. Some libraries are still in the transition phase toward library digitalization. Services related to local wisdom are still provided in various forms: manual, hybrid, and digital. Limitations in human resources, gaps in digital infrastructure, financial constraints, the professionalism of librarians, policies supporting cultural digitalization—both in terms of funding and respect for the rights of indigenous communities—and the digital literacy of library users remain issues that need to be addressed. The integration of local wisdom services and technology holds great potential for society and the academic world, which continues to evolve through digital humanities research. Therefore, a cross-sectoral collaborative approach is needed to achieve a harmonious implementation between modern library services and cultural preservation.